Building resilient food systems: An analytical review - Iyappan, Karunya; Babu, Suresh Chandra (International Food Policy Research Institute, 2018)
In this paper we undertake an analytical review of the extant literature on the building food system resilience. While the concept of food system resilience has become a topical issue in global and national policy discussion, there is little research on how to develop operational procedures to design and implement interventions from the food system and resilience perspective. This review identifies five major entry points to strengthen food system resilience in the national context: policy, institutions, technology, capacity, and governance. Measurement issues and analytical approaches to studying food system resilience are reviewed. We conclude that while there is a large gap in the methodological approaches to study the food system resilience, beginning with the case studies of understanding specific elements of a food system and their role in enhancing resilience would be good starting point for addressing thematic issues, challenges and constraints facing resilience of the food systems.